Idiopathic learning disability and genome imbalance. - Knight, S; Regan, R (2006)
Learning disability (LD) is a very common, lifelong and disabling condition, affecting about 3% of the population. Despite this, it is only over the past 10-15 years that major progress has been made towards understanding the origins of LD. In particular, genetics driven advances in technology have led to the unequivocal demonstration of the importance of genome imbalance in the aetiology of idiopathic LD (ILD). In this review we provide an overview of these advances, discussing technologies such as multi-telomere FISH and array CGH that have already emerged as well as new approaches that show diagnostic potential for the future. The advances to date have highlighted new considerations such as copy number polymorphisms (CNPs) that can complicate the interpretation of genome imbalance and its relevance to ILD. More importantly though, they have provided a remarkable approximately 15-20% improvement in diagnostic capability as well as facilitating genotype/phenotype correlations and providing new avenues for the identification and understanding of genes involved in neurocognitive function.